Estresse materno e estilos de apego em crianças obesas e eutróficas - Lima, Manuel Francisco de Araújo (2023)
Obesity, a multifactorial disease, is linked not only to dietary habits and sedentary lifestyle but also to psychological factors such as stress and attachment. This study explores the relationship between maternal stress, attachment, and childhood obesity, emphasizing the intergenerational transmission of these factors in understanding the disease. This study examined the relationship between maternal stress and attachment and childhood obesity. The sample comprised 102 female mothers or caregivers with biological bonds, of which 38 were mothers of healthy-weight children, and 64 were mothers of obese children, along with their respective children aged 6 to 11, enrolled in public schools in João Pessoa, totaling 204 participants. The instruments used included the Parental Bonding Instrument (PBI), Lipp's Inventory of Stress Symptoms for Adults (ISSL), and the Depression, Anxiety, and Stress Scale (DASS – 21) to assess mothers, and the Separation Anxiety Test (SAT) and Child Stress Scale (ESI) for the children. Mothers of obese children exhibited higher levels of stress and a higher BMI compared to mothers of healthy-weight children. Additionally, obese children showed a greater tendency towards insecure attachment. Insecure attachment in obese children was also significantly related to the employment status of the caregivers. These findings underscore the substantial influence of maternal behavioral and social factors, including stress, BMI, academic performance, and socioeconomic status, in the etiology of obesity and childhood attachment patterns.